2022
DOI: 10.1177/10775463221115451
|View full text |Cite
|
Sign up to set email alerts
|

Seismic control of the structures with active tuned mass damper and variable fractional order fuzzy proportional–integral–derivative controller

Abstract: The structural control of the building is a critical part of mitigating the catastrophic consequences of the earthquakes. The active control of structures has gained popularity in the construction industry because of its ability to adapt to different ground motion characteristics. The active tuned mass damper (ATMD) is one of the most versatile devices used for active structural control. This paper uses the ATMD and variable fractional order fuzzy PID (VFOFPID) controller for improving the performance of build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The effectiveness of hybrid LQR-PID compared to LQR showed that a newly proposed hybrid controller was able to reduce about 16% and 15% of the maximum displacement and maximum acceleration respectively, compared to the LQR controller. Other papers that proposed hybrid control strategy are Amini et al [24] with variable fractional order fuzzy PID (VFOFPID), Etedali et al [25] with fractional order PID (FOPID), and Baygi et al [26] with ANFIS-PID and Zand et al [27] with Robust PID. The control strategies used in structural control are summarized in Table 1 taken from the year 2018 until 2022.…”
Section: Hybrid Control Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of hybrid LQR-PID compared to LQR showed that a newly proposed hybrid controller was able to reduce about 16% and 15% of the maximum displacement and maximum acceleration respectively, compared to the LQR controller. Other papers that proposed hybrid control strategy are Amini et al [24] with variable fractional order fuzzy PID (VFOFPID), Etedali et al [25] with fractional order PID (FOPID), and Baygi et al [26] with ANFIS-PID and Zand et al [27] with Robust PID. The control strategies used in structural control are summarized in Table 1 taken from the year 2018 until 2022.…”
Section: Hybrid Control Strategymentioning
confidence: 99%
“…( 2018 PID-Fuzzy 4 Xu, Yu and Cui [28] 2018 H∞ 4 Heidari et al [23] 2018 LQR-PID 10 Etedali et al [25] 2018 FOPID 11 Jian et al [29] 2019 H∞ 3 Baygi et al [26] 2020 ANFIS-PID 4 Farzam et al [14] 2020 FLC 10 Khatibinia et al [17] 2020 OSMC 11 Zand et al [27] 2021 Robust PID 11 Eliasi et al [30] 2022 SMC, PID, LQR, FLC 11 Amini et al [24] 2022 VFOFPID 11…”
Section: Hybrid Control Strategymentioning
confidence: 99%